TEXT FORMING FUNCTIONS OF PREPOSITIONS - Abdulhakimova Sarvinoz Parda qizi; Ahmadaliyeva Khosiyatposhsha (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article describes in detail the text-forming properties of prepositions, their qualities as a lexical unit, their similarities and differences with other functional and meaningful words, the role of prepositions in text creation, and their role in a sentence.